2016
DOI: 10.4236/gep.2016.46008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Seasonal NDVI Change by GIS Geostatistical Analyst and Study on Driver Factors of NDVI Change in Hainan Island, China

Abstract: As Hainan Island belonged to tropical monsoon influenced region, vegetation coverage was high. It is accessible to acquire the vegetation index information from remote sensing images, but predicting the average vegetation index in spatial distributing trend is not available. Under the condition that the average vegetation index values of observed stations in different seasons were known, it was possible to qualify the vegetation index values in study area and predict the NDVI (Normal Different Vegetation Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…This, in turn, means that changes in vegetation dynamics are related to changes in the environment [10,[17][18][19][20]. Results of the use of NDVI indices in determining the area covered by vegetation found that the use of this index in quantitative indicators was effective [13]. NDVI indicators have been used to differentiate between green and non-green plants in the region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, means that changes in vegetation dynamics are related to changes in the environment [10,[17][18][19][20]. Results of the use of NDVI indices in determining the area covered by vegetation found that the use of this index in quantitative indicators was effective [13]. NDVI indicators have been used to differentiate between green and non-green plants in the region.…”
Section: Resultsmentioning
confidence: 99%
“…This made it necessary to learn the variance trend of NDVI in a region. We could qualify the NDVI value and predict the NDVI change trend if we knew the average NDVI value of each station during each of the distinct seasons [13]. Photosynthetically active irradiation of NDVI has been strongly correlated with vegetation biomass, green cover, and leaf area index.…”
Section: Introductionmentioning
confidence: 99%
“…Issues such as weak scale perception, limited data samples, and singular analysis approaches have arisen. However, GIS can facilitate comprehensive and precise quantitative analysis of high-density built environments through techniques such as big data processing and visualization [30], spatial morphology assessment [31,32], ecological environment monitoring [33], spatial element identification [34], and spatial statistical research [35]. In terms of emotional perception, traditional research methods typically fall into two categories: first, by constructing subjective indicators such as cognition and employing methods like questionnaire surveys to obtain respondents' emotional perceptions [36] and second, by collecting textual information such as travelogues and interviews from travel websites and inferring people's emotions towards cities or places through text analysis [37].…”
Section: Introductionmentioning
confidence: 99%
“…As respostas espectrais da vegetação são modificadas com base na densidade da folha e na estrutura do dossel. As diferenças relativas nas características espectrais vermelho (RED) e infravermelho próximo (NIR) formam a base de vários índices de vegetação, que são projetados para avaliar a condição da vegetação (LIU et al, 2016).…”
Section: Introductionunclassified